Understanding the Role of Nutrient Limitation on Plankton Biomass Over Arabian Sea Via 1‐D Coupled Biogeochemical Model and Bio‐Argo Observations. Issue 6 (11th June 2020) - Anju, M.; Sreeush, M. G.; Valsala, V.; Smitha, B. R.; Hamza, Faseela; Bharathi, G.; Naidu, C. V.
Abstract: Arabian Sea (AS) is known to have seasonal phytoplankton blooms during winter and summer driven by dynamically distinct physical forcing mechanisms and associated nutrient dynamics. A 1‐D coupled physical‐biogeochemical model based on North Pacific Ecosystem Model for Understanding Regional Oceanography (NEMURO) with nitrogen and silicon cycles is adapted for the AS environment. The model is implemented to investigate the role of nitrogen (nitrate + ammonium) versus silicate limitation on plankton biomass. The seasonal cycle of plankton biomass is well simulated by the model along bio‐Argo (during a period from 2013 to 2016) and ship cruise tracks (for the single year 2009). Further, three sensitivity simulations are conducted by suppressing (1) nitrate availability (representing new production), (2) ammonium availability (representing regenerated production), and (3) silicate availability (for diatom production). The new production represents 80% of the total primary production in the AS and implicitly controls 70% of total zooplankton production annually. The regenerated production augments small phytoplankton (by ~50%; e.g., flagellates) and small zooplankton (by ~20%; e.g., ciliates) growth with negligible effects on large phytoplankton (e.g., diatom) and predatory zooplankton (e.g., copepods). The diatom production remains within the observed range due to silicate limitation which is fundamental in the model for realistic simulation of chlorophyll. Silicate is the primary limiting nutrient in diatom bloom in the subsurface chlorophyll maxima with maximum limitation occurring during the winter season, due to the deeper silicicline as compared to shallower nitricline. At the surface, both nitrogen and silicate co‐limit the total production; however, nitrogen is a stronger limiter than silicate from March to June. The study highlights the relative role of silicate versus total nitrogen (nitrate + ammonium) in limiting primary production in the AS. Plain Language Summary: An intermediate complexity ecosystem model for ocean known as NEMURO is implemented for the Arabian Sea coupled with a 1‐D mixed layer model. The NEMURO model has 13 components of the ecosystem such as two functional groups of phytoplankton, three groups of zooplankton, dissolved and particulate organic matter, and sinking particle fluxes. The model predicts the plankton biomass evolution in the ocean by utilizing the light and nutrients for photosynthetic biomass production, grazing of phytoplankton by zooplankton, the cycling of nutrients via egestion, excretion, mortality, and remineralization. The NEMURO model utilizes silicate as a limiting nutrient for diatom production. Using this model, we have examined the potential role of silicate as a key limiting nutrient in the Arabian Sea productivity. We found that in the surface, both nitrate and silicate are equally limiting biomass production; however, nitrate appears to be a potential limiting nutrient than silicate from March to June. The study highlights the role of silicate versus total nitrogen in establishing the biophysical interactions between lower to upper trophic plankton biomass in the Arabian Sea. Key Points: New production supports ~80% of the primary production and controls ~70% of zooplankton biomass in the Arabian Sea annually The regenerated production supports ~50% of primary production of small phytoplankton and ~20% growth of small zooplankton The diatom bloom is colimited by nitrate and silicate at the surface, dominated by silicate limitation in the subsurface in Arabian Sea